2020
DOI: 10.31083/j.jin.2020.01.1203
|View full text |Cite
|
Sign up to set email alerts
|

TGM6 variants in Parkinson’s disease: clinical findings and functional evidence

Abstract: TGM6 encodes transglutaminase 6, which catalyzes the covalent crosslinking of proteins through transamination reactions. Variants in TGM6 have been identified as the cause of spinocerebellar ataxia type 35. However, we found 12 TGM6 variants of low frequency among 308 patients with Parkinson’s disease using next-generation sequencing technologies and multiple ligation-dependent probe amplification, including two variants TGM6 p.R111C and p.L517W, which have been reported to affect functions of transglutaminase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The clinical picture of a markedly asymmetric, progressive ataxia–dystonia syndrome with oculomotor apraxia and vertical supranuclear gaze palsy resembled NPC but was instead associated with a new pathogenic variant (T206P) in TGM6 , previously reported as the genetic etiology of SCA35, and with an unanticipated pathology consistent with PSP. While the clinical features were broadly compatible with the syndrome of spinocerebellar ataxia, SCA35 has never been reported to be associated with supranuclear gaze palsy (as per a systematic review of 66 cases reported; Supplementary Table S1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and Figure S1 ), nor with an underlying 4R tau proteinopathy compatible with PSP pathology. That said, in the background of severe DaT deficit on imaging and vertical supranuclear gaze palsy on examination, PSP was clinically excluded by the hyperkinetic rather than the parkinsonian phenotype, as well as the presence of appendicular and axial ataxia, which are exclusionary [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…The clinical picture of a markedly asymmetric, progressive ataxia–dystonia syndrome with oculomotor apraxia and vertical supranuclear gaze palsy resembled NPC but was instead associated with a new pathogenic variant (T206P) in TGM6 , previously reported as the genetic etiology of SCA35, and with an unanticipated pathology consistent with PSP. While the clinical features were broadly compatible with the syndrome of spinocerebellar ataxia, SCA35 has never been reported to be associated with supranuclear gaze palsy (as per a systematic review of 66 cases reported; Supplementary Table S1 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and Figure S1 ), nor with an underlying 4R tau proteinopathy compatible with PSP pathology. That said, in the background of severe DaT deficit on imaging and vertical supranuclear gaze palsy on examination, PSP was clinically excluded by the hyperkinetic rather than the parkinsonian phenotype, as well as the presence of appendicular and axial ataxia, which are exclusionary [ 16 ].…”
Section: Discussionmentioning
confidence: 93%
“…A total of 54 individuals (from 40 different families) with TGM6 variants were selected from 10 articles after excluding irrelevant articles and duplicate searches and including the clinical details of the case described above. 3 4 5 6 7 8 9 10 11 12 Out of these, one was a whole-exome sequencing-based clinical study to identify novel variants responsible for SCA, with a paucity of adequate clinical details, and the six cases identified in this study with TGM6 missense mutations were variants of uncertain significance. Hence, the six cases described in this study were excluded from the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“… 15 TGM6 is expressed in basal ganglia and cerebellum, especially in Purkinje cells, thereby explaining ataxia and parkinsonism in patients with pathogenic TGM6 variants. 3 4 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. Other candidate genes have recently been reported in different cohorts (i.e., RAD51B, 114 DYRK1A, 127 CHCHD2, 128 VPS35 (PARK17), 129,130 RAB39B, 131 TMEM230, 132 TGM6,133 …”
mentioning
confidence: 98%